Psychometric properties of the Czech Integrated Palliative Outcome Scale: reliability and content validity analysis - Vlckova, Karolina; Hoschlova, Eva; Chroustova, Eva; Loucka, Martin (BMC palliative care, 2020)
BACKGROUND: Outcome measurement is an essential part of the evaluation of palliative care and the measurements need to be reliable, valid and adapted to the culture in which they are used. The Integrated Palliative Outcome Scale (IPOS) is a widely used tool for assessing personal-level outcomes in palliative care. The aim of this study was to provide Czech version of IPOS and assess its psychometric properties. METHODS: Patients receiving palliative care in hospice or hospitals completed the IPOS. The reliability of Czech IPOS was tested with Cronbach alpha (for internal consistency), the intraclass correlation coefficient for total IPOS score and weighted Kappa (for test-retest reliability of individual items). Factor analysis was used for elucidating the construct (Exploratory Factor Analysis). Convergent validity was tested with correlation analysis (Spearman correlation) in a part of the sample, who completed also the Edmonton Symptom Assessment System (ESAS) and the Palliative Performance Scale (PPS). RESULTS: The sample consisted of 140 patients (mean age 72; 90 women; 81% oncological disease). The Cronbach alpha was 0.789; intraclass correlation was 0.88. The correlations of IPOS with ESAS was R = 0.4 and PPS R = - 0.2. Exploratory factor analysis revealed a 2-factor solution on our data. The first factor covers emotional and information needs and the second factor covers physical symptoms. CONCLUSION: Czech IPOS has very good reliability regarding both internal consistency and test-retest reliability. Together with an item analysis results, we can conclude that the Czech adaptation of the tool was successful. The convergent validity needs to be assessed on the larger sample and the proposed 2-factor internal structure of the questionnaire has to be confirmed by using CFA.
Keywords: dospělí; Palliative Care; průzkumy a dotazníky; Female; Psychometrics; psychometrie; paliativní péče; Quality of Life; Adult; ženské pohlaví; Surveys and Questionnaires; Adolescent; Reproducibility of Results; kvalita života; lidé; hodnocení výsledků zdravotní péče; Aged, 80 and over; reprodukovatelnost výsledků; Male; Aged; Czech Republic; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; mladiství; Outcome Assessment, Health Care; Humans